2019
DOI: 10.1097/paf.0000000000000517
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Spermatozoa Detection

Abstract: Semen is crucial evidence for some sex crimes, with its sole confirmation being sperm detection. The success of sperm detection is dependent on all levels of preanalytic and analytic procedures. Specimen collection must be performed by well-trained and competent forensic physicians as well as forensic nurses, with preservation done properly before laboratory transfer. Laboratory procedures should consider archival sperm identification, by visualization, with adequate amounts separated from other cells to obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 69 publications
0
11
2
Order By: Relevance
“…Corradini et al [100] showed that buccal cells collected directly on to FTA mini cards (GE Healthcare) and stored for 11 years still provided good quantities of DNA and good-quality DNA profiles. In addition to these studies, Suttipasit [55] emphasised the need for appropriate long-term specimen preservation in order to be able to take advantage of potential future methodological advances to interrogate samples beyond current abilities.…”
Section: Storagementioning
confidence: 99%
See 1 more Smart Citation
“…Corradini et al [100] showed that buccal cells collected directly on to FTA mini cards (GE Healthcare) and stored for 11 years still provided good quantities of DNA and good-quality DNA profiles. In addition to these studies, Suttipasit [55] emphasised the need for appropriate long-term specimen preservation in order to be able to take advantage of potential future methodological advances to interrogate samples beyond current abilities.…”
Section: Storagementioning
confidence: 99%
“…A study by Kishbaugh et al [53] of 50 vaginal swabs from unique donors over the age of 18 years and relevant history, and a study by Sari et al [54] of 20 pre-pubescent (3-9 years), 20 post-pubescent (16-45 years) and 20 post-menopausal (50-75 years) females, help fill this knowledge gap, and thus, assist the accuracy of interpretation of immunochromatographic testing results. In addition, a review of current methods of sperm detection, factors affecting sperm detection, and recent advances in sperm detection utilising alternative methodologies is provided by Suttipasit [55].…”
mentioning
confidence: 99%
“…However, redness and swelling were not used as statistical data in the results. The anogenital area was divided into 10 subgroup sites: (1) labia majora, (2) labia minora, (3) hymen at 3-or 9-o'clock position, (4) hymen below 3-to 9-o'clock position, (5) Cotton swabs were used to collect evidence at the external and internal areas of the genitalia and anus. Blood and genital and culture swabs for STIs were obtained.…”
Section: Examining Physicianmentioning
confidence: 99%
“…(3) consensual or nonconsensual; (4) macroscopic inspection and/or use of colposcope and/or toluidine staining; (5) recording and interpretation of type of wounds by TEARS classification (T = tear, laceration, or incision; E = ecchymosis; A = abrasion; R = redness; and S = swelling) 20 ; (6) inclusion or exclusion of anal injury; and (7) time since incident (TSI).…”
mentioning
confidence: 99%
“…These assays, developed as part of the Sperm Hy-Liter product range, use anti-sperm monoclonal antibodies functionalised with Alexa 488 fluorophores to label sperm cells, allowing them to be visualized on glass slides using standard fluorescence microscopy [ 7 ]. However, despite initial promise, these techniques have yet to be widely adopted by the forensic community due to the high cost associated with antibody-based testing reagents [ 8 ].…”
Section: Introductionmentioning
confidence: 99%